Beyond productivity, does the adoption of agricultural technologies improve food consumption and reduce poverty? Empirical evidence from Benin - Nonvide, Gbêtondji Melaine Armel (My University, 2024)
Beyond productivity, does the adoption of agricultural technologies improve food consumption and reduce poverty? To provide answers to this, the paper used data from the household survey on the Comprehensive Food Security and Vulnerability Analysis (CFSVA) carried out in 2017 in Benin. Five agricultural technologies were considered in this study. First, an extended ordered probit model was estimated to analyze the impact of technology choice sets on food consumption groups (poor, limit and acceptable). Second, an extended probit model is employed to assess the impact on poverty status. The results show that the adoption of multiple technologies increases food consumption and reduces poverty among agricultural households in Benin. Combinations of technologies that enhance both food consumption and poverty status are irrigation and herbicide, irrigation and chemical fertilizers and improved seed and chemical fertilizers. Therefore, policy interventions should help farming households gain access to these improved technologies to improve food security and reduce poverty.
Keywords: Agricultural technologies; extended regression models; food consumption; poverty; Benin